Maritime piracy in the Gulf of Guniea - Guedes, Henrique Portela (2020)
Maritime piracy dates back to the beginnings of maritime navigation, when the first commercial exchanges by sea began, having been considered practically extinct in the 19th century. It began to increase gradually from the end of the 1980s, however, the world only woke up to this reality with the outbreak of maritime piracy in the waters of Somalia in 2008. Since then, to this day, this phenomenon has become a serious threat to global maritime security. Currently, the Gulf of Guinea (GG) is the major concern of the international community, due to the high number of acts of piracy that have been registered there. This growth is due to several factors, mostly common to practically all the countries that are part of this Gulf, such as: deficient social policies, high corruption, high demography, high unemployment rates and huge proliferation of criminal networks. These are the factors that, associated with the lack of maritime policies on the part of the States in the region and of naval means to ensure the surveillance of their waters, have caused this area to register an increasing number of pirate attacks and, consequently, be considered as one of the most dangerous in the world for maritime navigation.